2021
DOI: 10.3390/cells11010070
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptomic and Functional Evidence Show Similarities between Human Amniotic Epithelial Stem Cells and Keratinocytes

Abstract: Amniotic epithelial stem cells (AESCs) are considered as potential alternatives to keratinocytes (KCs) in tissue-engineered skin substitutes used for treating skin damage. However, their clinical application is limited since similarities and distinctions between AESCs and KCs remain unclear. Herein, a transcriptomics analysis and functional evaluation were used to understand the commonalities and differences between AESCs and KCs. RNA-sequencing revealed that AESCs are involved in multiple epidermis-associated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 56 publications
(84 reference statements)
0
2
0
Order By: Relevance
“…This agrees with the estimated value of LC50 for human hair follicle stem cells, which is lower than the value obtained for keratinocytes. Moreover, we observed that at-RAL treatment greatly increased the expression of the ABCA4 gene in keratinocytes and that following at-RAL treatment, the expression of the ABCA4 gene in keratinocytes positively correlated with the expression of the INV gene (marker of differentiation) (Figure 7) and negatively correlated with the KRT5 gene activity, which is a marker of undifferentiated basal stem cells and reflects their proliferative capacity [30]. These results were sustained in concordance with the observation that retinal was transformed into retinoic acid more slowly in non-differentiating keratinocytes than in differentiating ones [31], and only keratinocytes that already committed to terminal differentiation can express an enzymatic system catalyzing the conversion of retinol into retinoic acid.…”
Section: Discussionmentioning
confidence: 86%
“…This agrees with the estimated value of LC50 for human hair follicle stem cells, which is lower than the value obtained for keratinocytes. Moreover, we observed that at-RAL treatment greatly increased the expression of the ABCA4 gene in keratinocytes and that following at-RAL treatment, the expression of the ABCA4 gene in keratinocytes positively correlated with the expression of the INV gene (marker of differentiation) (Figure 7) and negatively correlated with the KRT5 gene activity, which is a marker of undifferentiated basal stem cells and reflects their proliferative capacity [30]. These results were sustained in concordance with the observation that retinal was transformed into retinoic acid more slowly in non-differentiating keratinocytes than in differentiating ones [31], and only keratinocytes that already committed to terminal differentiation can express an enzymatic system catalyzing the conversion of retinol into retinoic acid.…”
Section: Discussionmentioning
confidence: 86%
“…Epidermis development, stratification and differentiation is a dynamic process, 32 in the future, enhancing the therapeutic potential and developing new clinical protocols are needed for the application of hAESCs‐based strategies in regenerative medicine.…”
Section: Discussionmentioning
confidence: 99%